Characteristic Image Findings of the Nasopalatine Duct Region Using Multidetector-Row CT - Kawashima, Yusuke; Kaneda, Takashi; Ito, Kotaro; Okada, Hiroyuki; Hirahara, Naohisa; Sakae, Toshiro; Muramatsu, Teruaki (Journal of Hard Tissue Biology, 2016)
Distinguishing normal parts of the nasopalatine duct from nonodontogenic nasopalatine duct cysts can be difficult. This study aimed to establish the characteristic imaging findings of the nasopalatine duct region on multidetector-row computed tomographic (MDCT) images. The subjects were 122 patients (61 males, 61 females; mean age, 49.8 years; age range, 17-88 years) who underwent 64-MDCT imaging of the maxilla after providing informed consent. Anatomic variants of the nasopalatine duct were classified using coronal slices. Measurements of the duct width diameters and the distances from the nasopalatine foramen to the incisive foramen as a major axis were performed using sagittal and coronal slices. CT values for the duct portion with maximum diameter were measured using axial slices. Regarding anatomic variations, 69 patients (56.5 %) had a single duct, 13 patients (10.7 %) had two parallel ducts, and 40 patients (32.8 %) had Y-type ducts. The mean width diameter of the nasopalatine duct on sagittal slices was 3.2 mm in the nasopalatine foramen, 2.7 mm in the middle point, and 3.1 mm in the incisive foramen. The mean width diameter of the nasopalatine duct on coronal slices was 4.3 mm in the nasopalatine foramen, 3.6 mm in the middle point, and 3.8 mm in the incisive foramen. The mean CT value in males and females was 122.4 ± 77.9 HU. Although the nasopalatine duct shows great variability in morphological appearance, characteristic findings for the nasopalatine duct region on MDCT images have been established in this study.